Cultural ecosystem benefits of urban and peri-urban greeninfrastructure infrastructure across different European countries - O'Brien, L.; De Vreese, R.; Kern, M.; Sievanen, T.; Stojanova, B.; Atmış, E. (Elsevier Gmbh, 2017)
Green Infrastructure within urban areas has become increasingly important in recent years. There has been the development of a European Commission green infrastructure strategy and a range of initiatives identifying the importance of green infrastructure. This paper explicitly identifies the cultural ecosystem benefits gained from urban and peri-urban green infrastructure drawing on studies undertaken in different European countries. The paper utilises the cultural ecosystem services framework developed in a United Kingdom National Ecosystem Assessment project. A review of literature identified studies from fifteen different countries and explores linkages between the types of green infrastructure, the practices undertaken in these spaces and the cultural ecosystem benefits gained. The results show that there are few detailed linkages made between the types of green infrastructure and the practices and benefits associated with these. The cultural ecosystem framework provides an important conceptual approach and this paper is one of the first to populate the framework in greater detail. Further research is needed to assess the differences in benefits and practices associated with different types of green infrastructure. A key message is that the cultural ecosystem benefits identified are wide ranging, diverse and multiple. The typologies and conceptual matrix developed in this paper could be utilised by green infrastructure practitioners to assist them in taking account of cultural ecosystem benefits in their management decision making processes. Crown Copyright (C) 2017 Published by Elsevier GmbH. All rights reserved.
Keywords: Green Space; Services; Forests; Woodlands; Health; Values; Areas; Recreation; Frequency; England